1966
DOI: 10.1073/pnas.56.1.72
|View full text |Cite
|
Sign up to set email alerts
|

Delayed hypersensitivity in vitro: its mediation by cell-free substances formed by lymphoid cell-antigen interaction.

Abstract: It has long been thought that delayed hypersensitivity is mediated by cells or cell-associated substances. In an attempt to investigate the mechanism of delayed hypersensitivity, in vitro studies using the inhibition of cell migration by specific antigen as an assay have been carried out. In this in vitro system, it has been shown that peritoneal exudate cells taken from guinea pigs exhibiting delayed hypersensitivity and placed in capillary tubes are inhibited from migration by specific antigen." 2 Moreover, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
612
1
8

Year Published

1970
1970
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,167 publications
(626 citation statements)
references
References 3 publications
5
612
1
8
Order By: Relevance
“…as yet, tmeharaeterized and apparently immunologically non-speeific migration stimtilatiort factors which act in vitro. As was shown in David's (1966) results, some ot the non-specific migration stimulation could be attribttted to variations between the protein concentration of "control" and "test" cultures. It remains to be shown whether other enhancing factors such as that described by Jatiis and Bach (1970), wliich potentiated antigen-induced lymphocyte transformation, also interfere with the MMI test.…”
Section: Iso-electnc Focussingsupporting
confidence: 60%
See 1 more Smart Citation
“…as yet, tmeharaeterized and apparently immunologically non-speeific migration stimtilatiort factors which act in vitro. As was shown in David's (1966) results, some ot the non-specific migration stimulation could be attribttted to variations between the protein concentration of "control" and "test" cultures. It remains to be shown whether other enhancing factors such as that described by Jatiis and Bach (1970), wliich potentiated antigen-induced lymphocyte transformation, also interfere with the MMI test.…”
Section: Iso-electnc Focussingsupporting
confidence: 60%
“…In some studies (Svejcar and Johanovsky, 1961;David, 1966), a non-specific migration stimulation was occasionally obscr\'ed when leucocvte.s were cultured with antigens to which they were not sensitized. Other workers (Federlin, Maini, Russell and Dumonde, 1971) have suggested that migration stimulation occurs when sensitized leucocytes are challenged in vitro with snb-optimal doses of antigen.…”
Section: Introductionmentioning
confidence: 99%
“…MIF was originally identified as a lymphokine that concentrates macrophages at inflammatory loci, is a potent activator of macrophages in vivo and is considered to play an important role in cell-mediated immunity. 3,10 Since the molecular cloning of MIF, 11 this cytokine has been reevaluated as a proinflammatory cytokine and pituitaryderived hormone that potentiates endotoxemia. 12,13 It has been shown that T cells and macrophages secrete MIF in response to various proinflammatory stimuli such as endotoxins.…”
Section: Discussionmentioning
confidence: 99%
“…24 Other retroviral vectors included those encoding CDK4, E2F1, and E2F4. For viral infections, 10 5 MEFs plated onto a 6-cm dish were incubated overnight with an appropriate amount of the corresponding retroviral stock. Cells were analyzed for the corresponding protein levels 3-4 days postinfection.…”
Section: Mice and Tissue Culturementioning
confidence: 99%
“…[1][2][3][4] MIF was originally identified as a product of activated T cells. 5 However, subsequent work showed that MIF is almost ubiquitously expressed in various tissues, including neural, epithelial, and hematopoietic lineage cells. [6][7][8][9] Studies using neutralizing antibodies implicated MIF in the development of pathologies of acute and chronic inflammation such as allograft rejection, wound repair, glomerulonephritis, inflammatory arthritis, and septic shock.…”
Section: Introductionmentioning
confidence: 99%